Comparative Study of National Education Standards among Three Large Islamic Foundations - Budi Utomo, Rukmono (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Generally, we know that there are three biggest islamic education foundations in Indonesia, i.e. Muhammadiyah through Majelis Dikdasmen PP Muhammadiyah, Nahdlatul Ulama (NU) through Ma’arif Education Unit (LP Ma’arif NU) and Al Azhar Islamic Boarding School (YPI Al Azhar). The aim of this research is for comparing National Education Standard among their foundations. This research called as comparative study and we use literature study as our method. Steps of our research starts from collecting information about amount schools of Majelis Dikdasmen PP Muhammadiyah, LP Ma’arif NU and YPI Al Azhar. After that, next we make percentage based on those amount schools and also try to get an information about National Education Standar and do comparative one each other. The emergency or the reason why this research has to be done is because people want to know what the different of schools under those three Islamic foundations. The result of this research generally say that schools under Majelis Dikdasmen PP Muhammadiyah using nation curriculum combined with Islam Muhammadiyah, Arabic and English language (ISMUBARIS), Schools under LP Ma’arif NU using Ahlussunah Waljamaah Curriculum and schools under YPI Al Azhar using nation curriculum combined Al Azhar Curriculum called as KP2M.